Systematic review and meta-analysis of the effects of blood flow restriction training on bone health in older adults - Liu, Yutong; Zhang, Yunfei; Wang, Tao; Gao, Zhendong; Wang, Xiaolin (Nature Research, 2025)
While low-intensity blood flow restriction (LI-BFR) training has recently been shown to improve bone health, there remains limited evidence regarding its impact on older adults. This meta-analysis aimed to quantitatively identify the effects of LI-BFR training on bone mineral density (BMD) and bone biomarkers compared with conventional resistance training programs. Studies were identified through searches of four databases: PubMed, Scopus, SPORTDiscus, and Web of Science. R packages were utilized for this meta-analysis. The results indicated that compared to low-intensity (LI) training, LI-BFR significantly increased BMD (ES = 0.25, 95% Confidence Interval [CI]: [0.08, 0.41], p < 0.01), osteotropic hormones (i.e., GH, ES = 1.18, 95%CI: [0.66, 1.70]), p < 0.001; IGF-1, ES = 0.89, 95% CI: [0.44, 1.33], p < 0.001), but resulted in a smaller increase in bone resorption markers (i.e., CTX, ES = -0.77, 95%CI: [-1.16, -0.37], p < 0.001). LI-BFR training demonstrated similar effects on BMD improvement as high-intensity (HI) resistance training (ES = -0.1, 95%CI: [-0.66, 0.41], p = 0.64). Furthermore, sex and training frequency moderated the secretion of osteotropic hormones (male vs. female: IGF-1, 0.51 vs. 1.64, p < 0.01; ≤ 3 times per week vs. > 3 times per week: GH, 1.62 vs. 0.68, p < 0.01, and IGF-1, 1.13 vs. 0.39, p < 0.05). In conclusion, LI-BFR training shows promise for enhancing bone health in older adults, offering benefits comparable to HI training.